Microscopic colitis: a common diarrhoeal disease. An epidemiological study in Örebro, Sweden, 1993–1998. (11th February 2004) - Olesen, M; Eriksson, S; Bohr, J; Järnerot, G; Tysk, C
Abstract : Background: Microscopic colitis, including collagenous colitis and lymphocytic colitis, mainly affects middle aged and older subjects, with a female predominance in collagenous colitis. The diseases have previously been regarded as rare. We present an epidemiological study of microscopic colitis in a well defined Swedish population. Methods: Patients were retrospectively searched for in colonoscopy reports of those who had a colonoscopy in the period 1993–1998 for non-bloody diarrhoea. All colonic mucosal biopsies were reassessed using strict diagnostic criteria. Results: Biopsies from 1018 patients were reassessed. Fifty one (45 female) collagenous colitis patients and 46 (31 female) lymphocytic colitis patients were diagnosed. Median age at diagnosis was 64 years in collagenous colitis and 59 years in lymphocytic colitis. The mean annual incidence of collagenous colitis was 4.9/10 5 inhabitants (95% confidence interval (CI) 3.6–6.2/10 5 ) and of lymphocytic colitis 4.4/10 5 inhabitants (95% CI 3.1–5.7/10 5 ). The annual incidence of collagenous colitis increased from 3.7/10 5 in 1993–1995 to 6.1/10 5 in 1996–1998 (difference 2.4/10 5 (95% CI −0.3–5.1/10 5 )) whereas the incidence of lymphocytic colitis increased from 3.1/10 5 to 5.7/10 5 (difference 2.6/10 5 (95% CI 0.1–5.2/10 5 )). Conclusions: The annual incidences of collagenous colitis and lymphocytic colitis are higher than considered previously and are now equal to the incidence of Crohn's disease in Sweden, and combined rates approach the incidence of ulcerative colitis. Microscopic colitis was diagnosed in 10% of all patients with non-bloody diarrhoea referred for colonoscopy and in almost 20% of those older than 70 years.